Evaluation of Protection Strategies Against Cyanide Exposure in Chemical Weapon Attack Scenarios: an Integrated Approach Between Security and Public Health - Rosyda, Esa Dina Inda; Prakoso, Lukman Yudho; Tasdik, Tasdik; Mahroza, Jonni Mahroza; Ruyat, Yayat; Hafizah, Mas Ayu Elita (Formosa Journal of Applied Sciences, 2024)
This integrated analysis explores real-world case examples and related data findings to gain a deeper understanding of the challenges and protection strategies needed to face these types of threats. The selected cases include the terrorist attack in Tokyo in 1995, the murder of Alexander Litvinenko in London in 2006, as well as the cyanide poisoning case in Jakarta in 2004. The data findings highlight the importance of developing rapid cyanide detection technology, personal protection equipment, coordinated emergency response, and effective law enforcement in protecting the public from cyanide exposure. Recommendations include investment in research and development of innovative protection technologies, development of standardized emergency response guidelines, and public outreach campaigns. With a holistic approach and cross-sector collaboration, it is hoped that we can increase preparedness and protect the community from the threat of chemical attacks involving cyanide.